Mapificación del grado de fertilidad de suelos mediante los sistemas de información geográfica sig del cantón Chilla provincia de El Oro - Caiminagua Paltin, Sergio Fabricio (2014)
This research work degree is the mapificación the degree of soil fertility as GIS Canton Chilla ,the study are aispolitically situated in the province of El Oro , Region seven Ecuador , has an area of ​​323.56 km2 , that in relation to the province accounts for 5.58% of the total area , the limits are: to the north by the Pasaje Canton on the south by the Zaruma and Atahualpa Cantons on the east by the Canton Zaruma and westbythe Canton Santa Rosa. The Geographic Information Systems (GIS ) have the ability to han large volumes of data and performincrea singly complex analysis. The principal components analysis and other statistical procedures were until recently few processes unless impossible to deal with information in a GIS have become a tool of paramount importance for precision agriculture ,becauseitallowsto capture, store , manage , manipulate and presentrelated and are useful elements in the ground surface data . The objectives were: 1. To determine the degree of soil fertility by texture analysis, pH, organic carbon, organic matter, cation exchange capacity, Ca + +, Mg + +, K + and Na + exchangeable, N, P, K and complementary Fe, Cu, Zn, Mn. 2. Develop through GIS maps texture, fertility, pH, organic carbon, organic matter, cation exchange capacity Ca + + , Mg + + , K + and Na + exchangeable, N, P, K, Fe, Cu, Zn and MnChilla canton. Protocols for soil analysis were: for organic matter, Walkley and Black, for mechanical analysis, Bouyucus, for cation exchange capacity, Formaldehyde, for exchangeable bases Na +, Ca + +, Mg + +, K +, the macro and micronutrients N, P, K, Ca, Fe, Cu, Zn, Mn, atomic absorption spectrophotometer: and pH, conductometer. With theresults, the following conclusions were reached :ThatChilla Canton soils , in 78.79 % of the total area are sandy textural class . That Organic Matter present in most of the surface of Canton Chilla is Very Low, thus the nitrogen level is also very low. The Cation Exchange Capacity in these soils ranges from very low to high with a slight majority of Low .Levels of exchangeable calcium and magnesium elements are Very High while Sodium and Potassium are Very Low .That the levels of macronutrients in soils are low Chilla Canton .Micronutrient levels and hadan irregular distribution of varying concentrations .That Chilla Canton soils are very acidic. That according to the classification of the degree of fertility of soils Codazzi of Colombia .Chilla Canton soils , has a fertility level Low.